Modulations of Saturn's UV Auroral Oval Location by Planetary Period Oscillations. Issue 2 (4th February 2019) - Bader, A.; Badman, S.V.; Kinrade, J.; Cowley, S.W.H.; Provan, G.; Pryor, W.
Abstract: It is well known that Saturn's magnetospheric dynamics are greatly influenced by the so‐called planetary period oscillations (PPOs). Based on Cassini Ultraviolet Imaging Spectrograph (UVIS) imagery, it has been shown previously that the UV auroral intensity is clearly modulated in phase with rotating field‐aligned current (FAC) systems associated with the PPOs. Here we expand upon this investigation by using the same data set to examine the PPO‐induced spatial modulation of the main auroral oval. We present a robust algorithm used for determining the location of the main emission in Cassini‐UVIS images. The location markers obtained are then used to calculate the statistical location of the auroral oval and its periodic displacement due to the PPO FACs and the related ionospheric flows. We find that the largest equatorward displacement of the main arc lags behind the PPO‐dependent statistical brightening of the UV aurora by roughly 45–90° in both hemispheres and is not colocated with it as the present model based on magnetometer observations suggests. We furthermore find the center of the auroral oval by fitting circles to the main emission and analyze its elliptic motion as the entire oval is displaced in phase with the PPO phases. It is demonstrated that the periodic displacements of both the auroral oval arc and its center are larger when the two PPO systems rotate in relative antiphase than when they are in phase, clearly indicating that interhemispheric PPO FAC closure modulates not only the intensity but also the location of the main UV auroral emission. Key Points: The UV main auroral oval is displaced from its statistical location due to PPO field‐aligned currents The northern oval is displaced nearly parallel to northern PPO dipole, the southern oval nearly antiparallel to southern PPO dipole Varying spatial oscillations for different PPO beat phases indicate interhemispheric PPO modulations